Moebius and Kallmann syndromes with diabetes insipidus: a phenotype of Fibroblast Growth Factor (FGF) 8 mutation - Omar , Ahmad Marzuki; Shahar, Mohammad Arif; Abd Wahab, Norasyikin; Mustafa, Norlaila; Sukor, Norlela; Kamaruddin, Nor Azmi (Malaysian Endocrine and Metabolic Society, 2014)
Moebius syndrome is a rare congenital condition typically characterised by congenital facial and abducens nerve palsies. Dysfunction of other cranial nerves, malformations of orofacial structures, and limb anomalies may also be present. The aetiology is not well understood, but may relate to chromosomal abnormalities and exposure to teratogens and vascular events during gestation. Kallmann syndrome, on the other hand, consists of congenital hypogonadotropic hypogonadism and anosmia. It represents a form of isolated GnRH deficiency. There have been several reported cases of Moebius syndrome associated with Kallmann syndrome, with one reported case of Moebius syndrome with diabetes insipidus and another of Kallmann syndrome with diabetes insipidus. We report a 30-year-old man who was born with left lower motor neuron facial, abducens and oculomotor nerve palsies, dental agenesis, hypogonadotropic hypogonadism with bilateral cryptorchidism and micropenis. His developmental milestones were delayed. At the age of 10 years old, he had progressive hearing loss following recurrent bilateral otitis media with effusion. A year later he was diagnosed with central diabetes insipidus and noted to have anosmia and bilateral optic disc coloboma. The pituitary MRI findings were normal. This case illustrates a rare combination of Moebius and Kallmann syndromes with diabetes insipidus, which may well describe the FGF8 mutation in this patient.